DAMPAK OVERPROTEKTIF TERHADAP PERKEMBANGAN KEMANDIRIAN ANAK - Kusumaningtyas, Lydia Ersta (Widya Wacana: Jurnal Ilmiah, 2015)
According to Enung Fatimah (2010: 202) overprotective is excessive protection ofchildren that can cause discomfort to them. While parents have to prove his role in givingaffection to their children by doing anything that is considered the best for the children, what isconsidered good sometimes not necessarily good for the children and sometimes children dowithout thinking beforehand whether the children like doing it or not. Overprotective is usuallydone by parents to their children who are still considered too young and usually unfavorable tothe development of the children’s independenceThe parents shall care for and protect children but it does not mean parents take overevery problems. Parents often intervene and resolve the problems of children which is actuallyless to educate children to be independent and responsible for their actions .Keywords : Overprotektive, Independence growth